NalO(4)/LiBr-mediated diastereoselective dihydroxylation of olefins: a catalytic approach to the prevost-woodward reaction - Emmanuvel, Lourdusamy; Shaikh, T. M. A.; Sudalai, A. (Organic Letters, 2005)
LlBr catalyzes efficiently the dihydroxylation of alkenes to afford syn and anti diols with excellent diastereoselectivity depending upon the use of NaIO4 (30 mol %) or Phl(OAc)(2) (1 equiv), respectively, as the oxidants. The oxidation of non-benzylic halides has been achieved for the first time to afford the corresponding diols in excellent yields.